2019
DOI: 10.1029/2018jb016904
|View full text |Cite
|
Sign up to set email alerts
|

Velocity‐Density Systematics of Fe‐5wt%Si: Constraints on Si Content in the Earth's Inner Core

Abstract: The elasticity of hcp-Fe-5wt%Si has been investigated by synchrotron X-ray diffraction up to 110 GPa and 2,100 K and by picosecond acoustics measurements at ambient temperature up to 115 GPa. The established Pressure-Volume-Temperature equation of state shows that the density of the Earth's inner core can be matched by an Fe-Si alloy with 5wt% Si for all reasonable core temperatures, but that its compressional and shear velocities remain too high with respect to seismological observations. On the other hand, F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
70
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 26 publications
(77 citation statements)
references
References 66 publications
6
70
1
Order By: Relevance
“…The measured d-spacing of the transient bcc {110} and {211} reflections corresponds to a hydrostatic pressure of 38 GPa; the high-pressure hcp {002} reflection corresponds to a pressure of 132±26 GPa using the 300 K static compression equation of state from Hirao et al 33 . We make no thermal corrections since the Hirao data agrees well with the shock Hugoniot data reported in Marsh et al 61 , as seen in Fig.4, for Fe-Si 6.9wt% ; measurements of Fe-Si 5wt% at slightly lower pressure by Edmund et al 65 suggest the thermal pressure is ∼15 GPa for our conditions, similar to that found by Fischer et al in Fe-Si 16wt% and less than our error bars. The inferred bcc pressure is consistent with our calculations for the transformation pressure described below.…”
Section: Discussionsupporting
confidence: 89%
“…The measured d-spacing of the transient bcc {110} and {211} reflections corresponds to a hydrostatic pressure of 38 GPa; the high-pressure hcp {002} reflection corresponds to a pressure of 132±26 GPa using the 300 K static compression equation of state from Hirao et al 33 . We make no thermal corrections since the Hirao data agrees well with the shock Hugoniot data reported in Marsh et al 61 , as seen in Fig.4, for Fe-Si 6.9wt% ; measurements of Fe-Si 5wt% at slightly lower pressure by Edmund et al 65 suggest the thermal pressure is ∼15 GPa for our conditions, similar to that found by Fischer et al in Fe-Si 16wt% and less than our error bars. The inferred bcc pressure is consistent with our calculations for the transformation pressure described below.…”
Section: Discussionsupporting
confidence: 89%
“…Irrespective of such considerations, for Fe-5Si, we observed that the acoustic travel time of a sample varied by nearly 50% from ambient pressure to 1 Mbar, while changes in sample volume led to variations in sample thickness of about 10% over the same pressure range [28]. Consequently, the primary contribution to the variation of the sample acoustic travel time over this pressure range was due to the change in sound velocity, rather than the change in thickness.…”
Section: Measurement Of the Sound Velocities Of Polycrystalline Fe-simentioning
confidence: 79%
“…The pressure dependence of the sample thickness was taken into account using P-V EoS determined by X-ray diffraction, either after [28] for the bcc and hcp phases of Fe10Si or after [27,29] for Fe5Si. We relate the pressure evolution of the longitudinal sound velocity to the pressure evolution of thickness and acoustic travel time using the following equation:…”
Section: Measurement Of the Sound Velocities Of Polycrystalline Fe-simentioning
confidence: 99%
See 2 more Smart Citations